(untitled) (Bangladesh Journal of Nuclear Medicine, 2026)
Lymphomas located in the orbit and surrounding structures are uncommon cancers, accounting for just 1% of all non-Hodgkin lymphoma cases. Most non-Hodgkin lymphomas of the orbit are classified as extranodal marginal zone B-cell lymphomas of mucosa-associated lymphoid tissue type. Due to the non-specific nature of the clinical signs and symptoms, there may be some delays in reaching a diagnosis. The purpose of our study is to evaluate the prognostic value of PET-CT after therapy, as well as the clinical course of lymphomas that involve the orbit. Bangladesh J. Nuclear Med. 29(1): 116-119, 2026